Information security culture in healthcare informatics: A preliminary investigation - Hassan N.H.; Ismail Z. (Asian Research Publishing Network, 2023)
Information security culture becomes an enabler towards an effective security practice. Human factors are recognised as one of the factors in addressing the issue of information security in healthcare informatics. Inculcating information security culture among healthcare practitioners is identified to be one of the solutions for a better security practice. Thus, identifying the issues and factors that influence information security culture are important. A preliminary investigation involving six healthcare professionals and academics have been carried out for better understanding on the critical factors that may influence the information security culture. In-depth interview method is chosen in this study. Thematic coding was conducted to characterise the themes and asses the factor that found to be influential. Results from the indepth interviews with healthcare expertise showed that four main themes may influence the degree to which information security may be cultivated. Security behaviour, security value, security awareness, and enforcement of security policy are the themes addressed by the key informants as the influential factors inculcating information security culture. This study also found that various level of healthcare professional exhibited different outcomes in information security culture. Findings from this study may provide guidance to the healthcare organisation to ensure their employee inculcate information security culture in holistic manner. 2005 2016 JATIT & LLS. All rights reserved.